Методи інноваційних технологій при підготовці фахівців технічної галузі - Луценко, А. В.; Чумак, В. С. (ДДМА, 2021)
Requirements for the quality of technical graduates are constantly growing, so today universities seek to follow the trends of scientific and technological progress. The paper considers the issue of improving the technical education of the population, in particular young people. Some methods of innovative technologies for introduction in training of experts of technical branch are resulted.
Keywords: інноваційні технології; освіта